CHOICE OF THE METHOD OF MATRIX REGISTRATION IN THE X-RAY RADIOMETRY ANALYSES OF NON-FERROUS METALS - YEFIMENKO, S.; REVA, M. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The method of spectral relations that allows to take into account the influence off stuff's material composition on the results of radiometry analysis of ores of non-ferrous metals multicomponent deposits is proposed.